Results of Archaeological Excavations Conducted at the Rakhat Monument in Almaty Region (Based on the Reporting Materials for 2015-2016) (Global Journal of Human-Social Science, 2019)
In the article was described the geographical location of the settlement area andunique features of the region Rakhat. During 1994-2005 settlement area was carried out archaeological excavation of the joint Kazakh-American expedition under the leadership by K.M. Baipakov, F
Keywords: archeology; geology - geomorphology; palynology; anthropology; climate; artifacts